Primary adherence to antidepressant prescriptions in primary health care: a population-based study in Sweden. (2nd January 2016) - Freccero, Carl; Sundquist, Kristina; Sundquist, Jan; Ji, Jianguang
Abstract: Background Medical adherence is important in the treatment of depression. Primary medical adherence, i.e. patients collecting their newly prescribed medications from pharmacies, is very different depending on the drug prescribedObjective To assess the rate of primary medical adherence in patients prescribed antidepressants and to identify characteristics that make patients less likely to pick up prescriptions.Methods An observational study was performed using primary health care data from Sweden on patients who were prescribed antidepressants. Univariate and multivariate logistic regression was used to determine differences in pick-up rate according to patient characteristics.Main outcome Pick-up rate, defined as collection of a prescription within 30 days.Results A total of 11 624 patients received an antidepressant prescription during the study period, and the overall pick-up rate was 85.1%. The pick-up rate differed according to country of birth: individuals born in the Middle East and other countries outside Europe had lower primary medical adherence than Swedes, with adjusted odds ratios (ORs) of 0.58 and 0.67, respectively. Patients at ages 64–79 years had a higher pick-up rate compared with those aged 25–44 years (OR 1.71). Divorced patients had a lower rate compared with married patients (OR 0.80).Conclusion Immigrants from the Middle East and other countries outside Europe and younger and divorced patients had lower primary medical adherence, which calls for clinical attention and preventive measures. Key points: Primary medical adherence is important in the treatment of depression. Are patient characteristics associated with primary medical adherence? The overall primary medical adherence rate was 85%. The rate differed by country of birth, age at diagnosis of depression, and marital status. Clinical attention is needed in patients who do not pick up their antidepressants.